Multiproduct Quality Competition:Fighting Brands and Product Line Pruning - Johnson, Justin P; Myatt, David P (American Economic Review, 2003)
Firms selling multiple quality-differentiated products frequently alter their product lines when a competitor enters the market. We present a model of multiproduct monopoly and duopoly using a general “upgrades” approach that yields a powerful analytical framework. We provide an explanation for the common strategies of using “fighting brands” and of product line “pruning.” The optimal strategy depends on whether entry prompts an incumbent to expand or contract its total output. We also present a general condition that guarantees that a monopolist will sell but a single product. Our model addresses other issues, including intertemporal price discrimination and “damaged goods.”